2018
DOI: 10.1016/j.socscimed.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and leukocyte glucocorticoid sensitivity: Implications for birth timing

Abstract: Rationale. Psychological stress-induced cortisol elevations appear to contribute to preterm birth. Yet, some studies suggest that the biological ramifications of racial discrimination-associated stress are unique and may involve development of decreased glucocorticoid sensitivity despite normalized cortisol levels. Objective. In this study, we examined the effects of racial discrimination on maternal cortisol output, leukocyte glucocorticoid sensitivity, and the degree of correspondence between cortisol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 59 publications
(74 reference statements)
1
28
0
Order By: Relevance
“…Across the 16 studies included, sample characteristics (including race/ethnicity and sex) varied, which may have obscured subpopulation‐specific findings. In a novel study on leukocyte glucocorticoid sensitivity and racial discrimination among 91 African American women, Gillespie and Anderson 1 found that decreased GC sensitivity was associated with a higher frequency of experiences with racial discrimination. Experiences of discrimination have also been linked to preterm birth among African American women 54 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the 16 studies included, sample characteristics (including race/ethnicity and sex) varied, which may have obscured subpopulation‐specific findings. In a novel study on leukocyte glucocorticoid sensitivity and racial discrimination among 91 African American women, Gillespie and Anderson 1 found that decreased GC sensitivity was associated with a higher frequency of experiences with racial discrimination. Experiences of discrimination have also been linked to preterm birth among African American women 54 …”
Section: Discussionmentioning
confidence: 99%
“…Alterations in glucocorticoid (GC) sensitivity may occur as a result of chronic stress, including that due to racial discrimination, and thus may be implicated in the persistent adverse maternal and infant health outcomes of African Americans 1 . Despite the appeal of this mechanism, there are many gaps in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to encourage the USA to ratify its constitution in 1946, and to avoid a repeat of the pre-war period, when it had refused to join the League of Nations, the WHO avoided direct engagement with the subject of healthcare financing, restricted to a 'study and report' role. 19 This left the ILO as the de facto UN agency with power to directly advise governments on health financing, albeit solely in relation to social security. From the outset, this led to some friction with the WHO, which had direct responsibility for international health.…”
Section: The Ilo and Healthcare Financingmentioning
confidence: 99%
“…This is evident from the WHO's hostile reaction to the report of the Commission on Organisation of Medical Care (COMC) in 1952. 48 Initiated in response to the ILO's draft social security convention, the COMC featured prominent interwar advocates of social medicine such as Henry Sigerist and Ren e Sand. The Commission advanced proposals, which were anathema to organised interests such as the American Medical Association, such as universal healthcare, salaried medical services and group practice.…”
Section: Pragmatic Gradualism 1952-1959mentioning
confidence: 99%